HAJI DENGAN HUTANG: ANALISIS KONSEP ISTIṬĀ‘AH AL-MĀLIYAH PERSPEKTIF MUHAMMAD BIN IDRIS ASY-SYAFI‘I DAN PETUGAS HAJI - Farizha Nafillah Sahri; Imron Mustofa; Enggita Dwi Anggraini (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
Hajj is a fundamental pillar of Islam that every Muslim is obligated to fulfill if they meet the necessary conditions. However, in its practice, there are still issues that need attention, one of which is funding the Hajj pilgrimage through debt. This issue is important to be studied more deeply, considering that the Hajj pilgrimage requires adequate financial capacity so as not to burden oneself or one's family after returning from the holy land. This study aims to analyze the concept of istiṭā‘ah al-māliyah (financial capability) in the perspective of Imam Muhammad ibn Idrīs Ash-Shāfi‘ī and compare it with the views of Hajj officials regarding the practice of taking debt for Hajj. According to Imam Shafi‘i‘s view, financial capability is a mandatory requirement for someone who wants to perform Hajj. He also emphasized that financial capability not only covers the cost of travel and necessities during the pilgrimage, but also ensures that one is not in a state of deprivation or debt after returning from Hajj. This shows how important economic balance is for prospective pilgrims, both before and after the pilgrimage. In addition, this study also uses interview data with one of the hajj officers, those who play a key role in applying the concept of istiṭā‘ah in practice. Hajj officers have a crucial responsibility to provide a clear and in-depth understanding of istiṭā‘ah al-māliyah to prospective pilgrims. This is so that they can make wise decisions and avoid financial burdens which could potentially lead to issues in the future.